Content related to oral health informatics and promotion: A systematic review - Diana Constance; Rohini Subbiah; Parangimalai Diwakar Madan Kumar; Aparna Sukumaran (Wolters Kluwer Medknow Publications, 2024)
Social media is a technology that supports the sharing of content, multimedia, and information through virtual networks and communities. The aim of this study was to determine the role of Twitter in oral health information and promotion. This systematic review was carried out using a transparent methodology in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. An extensive literature search was carried out in PubMed, Trip database, and Google Scholar database from the year 2006 to 2023. The search generated 1901 articles. Five articles were selected for this review. The majority of the articles in this review demonstrated a positive association between Twitter and the promotion of oral health by assessing oral health campaign tweets and emotional experiences shared regarding people's dental health.